An Integrative Law Theory Approach to Address Corruption in Indonesia’s Social Security Agency for Health - Abidin, Zainal; Fikri, Ahmad Ma’mun (Research Horizon, 2025)
Corruption in Indonesia’s health sector remains high, scoring 34/100 in 2023 and ranking 115th out of 180 countries, undermining the quality of health insurance services and social protection. This study aims to address corruption at the Social Security Agency on Health using the Integrative Law Theory. A normative legal method with comparative and conceptual approaches was applied to qualitatively analyze corruption issues. Findings show that Denmark enforces strict anti-corruption laws emphasizing transparency, accountability, integrity, independent oversight, and international cooperation. In Indonesia, anti-corruption regulations include the Corruption Eradication Law, the Corruption Law, and the role of the Corruption Eradication Commission, supported by regulations on public service and procurement. Applying Integrative Law Theory at the Social Security Agency on Health involves combining legal principles, local values, and multidisciplinary approaches, including enhanced transparency, robust internal oversight, non-litigation strategies, dynamic policy adaptation, and alignment with Pancasila values. Adopting these measures is expected to strengthen organizational integrity and improve the effectiveness of public fund management.